Comparative karyomorphological analysis of two varieties of Brassica campestris from Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2021)
Two varieties of the oilseed plant viz. Brassica campestris var. Tori-7 and Brassica campestris var. BARI Sarisha-9 were karyomorphologically investigated following orcein staining. Presence of “Round Pro-chromosome Type” of interphase nuclei and “Continuous Type” of prophase chromosomes indicating that both Tori-7 and BARI Sarisha-9 were originated from common ancestor. Moreover, both the varieties were found to possess 2n=20 chromosomes with almost similar range of length i.e.; 0.90±0.04-2.51±0.05μm for Tori-7 and 0.99±0.06-2.60±0.06μm for BARI Sharisha-9. The total length of 2n chromosome complement was recorded as 29.61±0.76μm for Tori-7 and 29.75±0.80μm for BARI Sharisha- 9 where a slight gradual decrease of chromosomal length was observed in both cases. Average chromosomal length, range of individual chromosomal length, relative length and centromeric index of both varieties were more or less similar. Karyotype symmetry index and Karyotype asymmetry index indicating the symmetric nature of both varieties. All metacentric chromosomes were found in Tori-7 representing strictly symmetric karyotype. Beside metacentric, 2 sub-metacentric chromosomes were found in BARI Sharisha-9 representing almost symmetric karyotype. Thus the two varieties of Brassica campestris -were plants of primitive nature. However, BARI Sharisha-9 can be considered comparatively advanced than Tori-7 based on different cytogenetical features. Therefore, the compilation of these karyomorphological information will be useful for authentic identification and characterization of the two varieties of Brassica campestris which are very basic and important information for breeding in crop improvement programme.Jahangirnagar University J. Biol. Sci. 9(1 & 2): 69-77, 2020 (June & December)